EVOLVING UNITED STATES POLICY TOWARD THE CASPIAN REGION: A DELICATE BALANCE - IBRAHIM, Azeem (CENTRAL ASIA AND THE CAUCASUS, 2007)
Historically, the United States had almost no involvement in the Caspian Sea region, which was so remote both in geographical and cultural terms that the U.S. government was barely aware of its existence. The 19th century “Great Game” of power politicking between Russia and Great Britain over the region took place before the United States had emerged as a world power, and it had at best a marginal role in this episode. Even when the United States became a major power, it focused its attention on the western hemisphere and events in its own backyard.The same could not be said of the actions of Russia in Manchuria at the time, and United States involvement in the Manchurian dispute brought the realization home to the Americans that in future Russia would be its major rival on the world stage.1 Even at times in the following century when the two powers cooperated, such as during World War II, their alliance was based more on strategic needs than on deep-seated conviction. The wartime military cooperation soon gave way to the Cold War, which lasted for most of the rest of the 20th century and affected most corners of the globe. The Caspian region was heavily dominated by Russia, with most of its territories comprising Soviet Republics. American activity there was nonexistent.